Sample Preparation for Detection of Different Bacterial Strains by Matrix‐Assisted Laser Desorption/Ionization Time‐of‐Flight (MALDI‐TOF) Mass Spectrometry. Issue 8 (9th August 2021) - Chac, Denise; Kordahi, Melissa; Brettner, Leandra; DePaolo, R. William
Abstract: Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) provides a fast and easy means to identify culturable microorganisms to the species level. The sample preparation of microbial colonies for MALDI‐TOF analysis requires a suitable protein extraction method. While standard MALDI‐TOF sample preparation methods are well suited for the identification of and the discrimination between microorganisms belonging to different species, they are not disruptive enough to allow the discrimination between different strains of the same microorganism. More disruptive protein extraction methods lead to better discrimination power because they allow a better breakdown of bacterial cell membrane and a more efficient extraction of conserved microbial proteins that are specific to each species and strain. Here we describe how to extract proteins from single microbial colonies using formic acid and acetonitrile to disrupt cells prior to placing them on a target plate for MALDI‐TOF MS analysis. Contrary to other sample preparation methods for MALDI‐TOF MS, this approach allows the discrimination between different strains of microorganisms of the same species. Our approach also provides the groundwork data for building algorithms that allow the detection of specific microbial strains of interest, with a great potential for diagnostic applications in clinical settings. © 2021 Wiley Periodicals LLC. Basic Protocol : Protein extraction and MALDI‐TOF bio‐typing of phenotypically distinct bacterial species